Rational Gridlock. - Edgar, Patrick B. (University Press of America, 2011)
This book describes how rationality undermines bureaucracy's ability to solve problems or to gain the confidence of the general public. The author suggests ways to change the bureaucratic environment into one that appreciates the creative abilities of all its members, without the false premise of operating government like a business.